The role of intellect in the scientific and creative activity of students - Kholbutaevna, Kholnazarova Matlyuba; Ayubovna, Fayzieva Shoira; Mamatmuratovna, Kholnazarova Dildora; Farmanovna, Babajanova Fotima (International Journal of Psychosocial Rehabilitation, 2020)
This article provides a psychological analysis of the importance of intellect in the scientific and creative activity of the individual. Ways to develop students' creativity are shown. It also analyzes the successful development of creative qualities, important levels of creative potential of the individual, the stages of formation of the creative personality. In their research activities, students studied the analogy with the general intellect, the separation of concepts according to important features, the correlation between visual thinking. The results of students in the areas of study were analyzed, which proved to reflect the same level in solving tasks related to complex analogies. According to a complex analogy, there was a difference in the performance of students in the natural direction and the humanities. It has been proven that in the research activities of students of the natural direction, the general intellect reflects the inverse relationship with the practical intellect. Conclusions and recommendations on the formation and development of scientific creativity of the person are given.